Children’s Religious Rights in School: Religious Education, Display of Religious Symbols and Religious Clothing in Schools - Schanda, Balázs (Religion and Children's Rights, 2025)
Abstract:From the outset, religious entities have played a central role in education. Despite significant national and regional differences, a number of Catholic religious orders and Protestant schools have shaped the education system in most European countries. Introducing compulsory education (mostly in the 18th century) did not change the central role of denominations in the education system. Across Eastern Europe, the communist regime has curtailed the role of churches in education as well as the possibility of churches providing religious education in public schools. Since the collapse of the communist system, various schemes of religious education were reintroduced in public schools, and religious communities were once again considered important service providers in the education system. Symbols carrying cultural identity—often linked to religion—may have reappeared in schools; in this respect there are significant national differences. Participation in religious education at public schools generally depends on parental decision. Considering the limited presence of Islam in the eastern part of Central Europe, the issue of Islamic headscarf at schools has yet to become a subject of wider public debate. Schools have remained the most important institution of society where generations growing up learn to live together in harmony.Keywords: school, religious education, ethics, church schools, religious symbols, religious garment